Recurrent, bilateral, and metastatic pheochromocytoma in a young patient with Beckwith-Wiedemann syndrome: A genetic link? - Caza, Tiffany; Manwaring, Jared; Riddell, Jonathan (Canadian Urological Association Journal, 2017)
Beckwith-Wiedemann syndrome (BWS) is a genetic disorder at chromosome 11p15 that leads to increased activity of insulin-like growth factor-2 (IGF2) and reduced activity, with no active copy of the inhibitor of cell proliferation, CDKN1C, resulting in excessive growth and increased risk of tumour formation. Isolated cases of patients with Beckwith-Wiedemann syndrome and pheochromocytoma are reported in the literature; however, none have described a molecular or cytogenetic evaluation for associated genetic abnormalities. We present a case of an adolescent female with Beckwith-Wiedemann syndrome who developed recurrent, bilateral, and metastatic pheochromocytoma despite low-risk histopathology. Genotyping studies, which evaluated for genetic predisposition to pheochromocytoma or paraganglioma (PHEO/PGL), including the PGLNext sequencing panel of 12 associated genes, and a whole genome comparative genome hybridization microarray, were performed. Genomic studies were unexpectedly negative. Additionally, the histopathology of the PHEO/PGL of our patient had low-risk features, which is unusual in cases of metastases, occurring in less than 4% of cases.1 This case suggests that the BWS in itself could predispose to formation of a PHEO/PGL phenotype with aggressive behaviour. The following manuscript summarizes the case report, reviews pertinent literature, and proposes a possible mechanism for this association.